Seed treatment with Bacillus bacteria improves maize production: a narrative review - Ocwa, Akasairi; Ssemugenze, Brian; Harsányi, Endre (Acta Agraria Debreceniensis, 2024)
Maize (Zea mays L.) is an important crop in relation to its production and consumption. Production of maize is constrained by soil infertility and poor quality seed. Microbial technologies like seed treatment with Bacillus bacteria improves the productivity of maize on infertile soil. However, due to variations in maize growth environments and Bacillus species, this review was conducted to identify the common species of Bacillus species used for seed treatment, and provide an overview of the effect of seed treatment with Bacillus on maize growth and yield. Results show that Bacillus subtilis, Bacillus pumilus and Bacillus amyloliquefaciens were the dominant species used for seed treatment. Bacillus was used as both a biofertiliser and biopesticide. The conspicuous positive effects of Bacillus were in plant height, shoot and root length, and shoot dry matter depending on the species. In terms of grain yield, Bacillus subtilis (8502 kg ha-1), Bacillus amyloliquefaciens (6822 kg ha-1) and Bacillus safensis (5562 kg ha-1) were the bacterial species that had an overall pronounced effect. The highest increase in grain yield was in the interactive effect of Bacillus megaterium + Bacillus licheniformis (18.1%) and sole Bacillus subtilis (15.6%), while Bacillus pumilus reduced grain yield by 4.8%. This shows that the improvement of maize productivity using Bacillus bacteria requires careful selection of the species for seed treatment.